Application of Anharmonic Correlated Debye Model in Investigating Anharmonic XAFS Thermodynamic Properties of Crystalline Silicon - Tien, Tong Sy (VNU Journal of Science: Mathematics - Physics, 2022)
In this work, the temperature dependence of the anharmonic X-ray absorption fine structure (XAFS) and thermodynamic properties of the crystalline silicon (c-Si) have been investigated. The thermodynamic parameters are derived from the influence of the absorbing and backscattering atoms of all their nearest neighbors in the crystalline lattice with thermal vibrations. The Debye-Waller factor and thermal expansion coefficient in the anharmonic XAFS of c-Si were calculated in explicit forms using the anharmonic correlated Debye (ACD) model. This calculation model is developed from the many-body perturbation approach and correlated Debye model using the anharmonic effective potential. The numerical results of c-Si in temperature ranging from 0 to 1500 K are in good agreement with those obtained by the other theoretical procedures and experiments at several temperatures. The analytical results showed that the ACD model is useful in analyzing the experimental XAFS data on c-Si.